Soil Color and US Northeast Aquods. Issue 4 (15th June 2016) - Stolt, Mark H.; Rabenhorst, Martin C.; Ghabbour, Elham A.; Davies, Geoffrey
Abstract : Core Ideas: Identifying hydric soils and depth to seasonal high water table is difficult in Spodosols. The specific criteria for classifying wet Spodosols need to change. Extractable Fe does not appear to contribute to the red color of wet Spodosols. An interaction between Al and humic substances may possibly contribute to the redder hues. Aquods commonly occur in wetland settings across a range of temperature regimes. Understanding their morphologies is critical to developing effective hydric soil indicators. In this study, we examined a range of wet Spodosols of the northeastern United States. We tested whether the red hues associated with wet spodic horizons are a function of humic (HA) and fulvic acids (FA) or Fe, and addressed questions related to hydric soil indicators, horizon designation, and soil classification. Only two of the 11 seasonally saturated Spodosols met current criteria for Aquods. Almost all of the 24 Bh, Bhs, or Bhsm horizons had 3 to 10 times more ammonium oxalate extractable Al than Fe (mean Fe was <0.15%), yet only three pedons met the current criteria for "Al" great groups. We found no consistently applied color or sesquioxide content criteria for separating Bh from Bhs horizons. These results suggest that criteria for horizon designation and classification of Aquods need to be reconsidered. There were no relationships between extractable Fe and hue ( p = 0.50). Weak correlation coefficients (−0.40 and −0.39; p = 0.051 and 0.057) between hue and FA and HA suggest little support for red hues being primarily a function of HA or FA. The significant relationship between Al and hue (−0.46; p = 0.025) and the strong correlation between Al and both HA and FA (0.87 and 0.86; p < 0.001) suggest a possible interaction between Al and the humic substances resulting in redder hues. We found more than twice as much HA in the spodic horizons as FA and concluded that FA is the precursor of HA in US Northeast spodic horizons.